2003
DOI: 10.2116/analsci.19.1663
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Bisphenol A and 4-Nonylphenol in Human Milk Using Alkaline Digestion and Cleanup by Solid-Phase Extraction

Abstract: A highly sensitive and selective method based on alkaline digestion for the simultaneous determination of bisphenol A (BPA) and 4-nonylphenol (NP) was developed. The method consists of digestion of the matrix with ethanolic KOH, extraction with diethyl ether under a mild alkaline condition, cleaning with successive aminopropyl (NH2) cartridges and derivatization followed by a GC-MS analysis. The assay accuracies, expressed as recoveries, were 82 -113% for BPA and 89 -97% for NP. The limits of detection of BPA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(38 citation statements)
references
References 21 publications
3
31
0
2
Order By: Relevance
“…Compared with other methods [10,13], our on-line SPE-HPLC-MS/MS method provides similar sensitivity, precision, and accuracy, without complicated and timeconsuming sample preparation. Our method can be used for quick, accurate, and cost-effective analysis of large numbers of samples in epidemiologic studies to assess the prevalence of infant exposure to selected phenols and chlorinated organic chemicals via breastfeeding.…”
Section: E-mail Address: Acalafat@cdcgov (Am Calafat)mentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with other methods [10,13], our on-line SPE-HPLC-MS/MS method provides similar sensitivity, precision, and accuracy, without complicated and timeconsuming sample preparation. Our method can be used for quick, accurate, and cost-effective analysis of large numbers of samples in epidemiologic studies to assess the prevalence of infant exposure to selected phenols and chlorinated organic chemicals via breastfeeding.…”
Section: E-mail Address: Acalafat@cdcgov (Am Calafat)mentioning
confidence: 99%
“…Interest in monitoring breast milk for environmental contaminants is increasing because breast milk is the main route of exposure to environmental chemicals for breastfed infants. Methods that have been reported use several analytical techniques to measure environmental phenols in milk [10][11][12][13]. BPA was measured by high performance liquid chromatography (HPLC) with column-switching and fluorescence detection [11]; and by alkaline digestion followed by solid-phase extraction (SPE), derivatization, and detection by gas chromatography-mass spectrometry (GC-MS) [10].…”
Section: E-mail Address: Acalafat@cdcgov (Am Calafat)mentioning
confidence: 99%
See 1 more Smart Citation
“…Data have been published regarding for instance the determination of bisphenol AF in both serum and urine of rats [9] or BPS, BPF, and BPB in human urine [10][11][12][13]. Several authors have also reported different analytical methods for the determination of BPA in breast milk [14][15][16][17][18][19][20][21][22][23]. Kuruto-Niwa et al [14] and Migeot et al [22] reported data for the determination of BPA in colostrum samples.…”
Section: Introductionmentioning
confidence: 99%
“…This analytical method has been widely used for the determination of BPA in different biological matrices in the framework of various cohort population studies. Samanidou et al [20] and Otaka et al [21] reported analytical methods based on MSPD and alkaline digestion, respectively, for the determination of BPA in breast milk samples. Cariot et al also reported an on-line SPE-ultra high-performance liquid chromatography (UHPLC)-MS/MS method from a 500-ÎŒL test sample with a limit of quantification (LOQ) of 0.4 ng mL −1 [18].…”
Section: Introductionmentioning
confidence: 99%